Strategy Rumah BUMN PLN dalam Pengembangan UMKM melalui Klusterisasi UMKM di Kabupaten Majene, Sulawesi Barat: Penelitian - Rizki Abdillah Tanjung; Sahrul Salam; Sudirman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of the number of MSMEs in Majene Regency continues to increase but is not followed by the development of these MSMEs. The MSME Clustering Strategy carried out by Rumah BUMN PLN Majene aims to develop MSMEs in Majene Regency, so that MSMEs continue to grow and their income increases. This type of research uses a qualitative descriptive method. Data collection techniques used are observation, interviews and documentation studies. Data analysis used is data reduction and conducting data validity with source triangulation techniques. The results of the study indicate that the MSME Clustering Strategy implemented by Rumah BUMN PLN Majene plays a role in developing MSMEs in Majene. MSME Clustering is carried out by grouping MSMEs into classes such as Bronze, Silver, Gold and Platinum. This clustering makes it easier for Rumah BUMN PLN to monitor the development of each MSME and determine the right activity program according to the needs of MSMEs.